Cisplatin and Irinotecan as First-Line Chemotherapy for Previously Untreated Metastatic Thymic Carcinoma: Updated Analysis - Fukuda, Akito; Okuma, Yusuke; Hakozaki, Taiki; Mirokuji, Kie; Yomota, Makiko; Hishima, Tsunekazu; Hosomi, Yukio (Frontiers in Oncology, 2022)
Platinum-based chemotherapy is the de facto standard treatment for metastatic or unresectable thymic carcinoma. The optimal chemotherapy regimen has not yet been determined, including whether this should be combined with a second- or third-generation anti-cancer agent. We retrospectively evaluated the data of patients with metastatic or unresectable thymic carcinoma who were treated with a combination of cisplatin and irinotecan as first-line chemotherapy between 2002 and 2021 (trial registration UMIN000012175). The primary endpoint was response rate according to the RECIST criteria version 1.1. Secondary endpoints were disease control rate, progression-free survival (PFS), overall survival (OS), and toxicity (adverse events). Some patients analyzed in this study were also included in the previous trial, which was terminated early. For this analysis, we included 18 patients with a median age of 56 years and an Eastern Cooperative Oncology Group performance status of 0 or 1. All patients had clinical stage IVa or IVb thymic carcinoma according to the Masaoka-Koga staging system. The response rate was 44% and the disease control rate was 89%. The median PFS was 8.4 months (95% confidence interval (CI): 2.7–11.6 months) and the median OS was 45.6 months (95% CI: 15.7–69.1 months). Grade 3 or worse hematological toxicity was observed in 5 patients and grade 3 or worse non-hematological toxicity was observed in 3 patients. None of the patients developed febrile neutropenia, and no treatment-related deaths occurred. Thus, the combination of cisplatin and irinotecan as first-line chemotherapy for metastatic thymic carcinoma showed efficacy and acceptable toxicity.